Dual impairments in visual and hearing acuity and age-related cognitive decline in older adults from the Rancho Bernardo Study of Healthy Aging. (18th January 2021) - Parada, Humberto; Laughlin, Gail A; Yang, Mingan; Nedjat-Haiem, Frances R; McEvoy, Linda K
Abstract: Background: We examined the associations between dual impairments in visual and hearing acuity and aging-related cognitive decline. Methods: This was a longitudinal study of adults who had visual and hearing acuity and cognitive function assessed in 1992–1996 and were followed for up to 24 years (mean = 7.3 years), with up to five additional cognitive assessments. Visual impairment was defined as vision worse than 20/40, hearing impairment as pure-tone average thresholds >25 dB. Associations were tested using linear mixed-effects regressions. Results: Of 1, 383 participants, 293 had visual impairment, 990 had a hearing impairment and 251 had both deficits. In fully adjusted models, low visual acuity was associated with poorer Mini-Mental State Examination (MMSE; β = −0.29) and Trail-Making Test Part B (Trails B; β = 13.22) performance, and with faster declines in MMSE (β = −0.12) and Trails B (β = 1.84). The combination of low visual and low hearing acuity was associated with poorer MMSE (β = −0.44) and Trails B (β = 11.20) scores, and with faster declines in MMSE (β = −0.19), Trails B (β = 3.50), and Verbal Fluency Test (VFT; β = −0.14) performance. Associations were similar in men and women. Conclusion: Impairments in both vision and hearing are associated with a more rapid decline in cognitive function with aging.